Groundwater quality analysis using different water quality indices in the hard rock aquifer region in semi-arid environment - Dimple; Pradeep Kumar Singh; Mahesh Kothari; Kamal Kishore Yadav; Sita Ram Bhakar (Water Supply, 2023)
The present study aimed to assess the groundwater quality in the hard rock aquifer system of the Nand Samand catchment for irrigation use by employing distinct water quality indices (sodium adsorption ratio, per cent sodium, electrical conductivity, residual sodium carbonate, soluble sodium per cent, Kelly's ratio, and permeability index) and also, using graphical illustration techniques (United States Salinity Laboratory (USSL) diagram, Piper, Gibbs, Wilcox, and Chadha diagram, Rajasthan, India. Groundwater samples were collected in two seasons, i.e., pre-monsoon and post-monsoon seasons (for the years 2019 and 2020). Ninety-five samples were collected and analyzed to assess overall groundwater quality for irrigation use. The USSL diagram indicated that the maximum groundwater samples were classified under categories C3S1 and C4S1 during the pre-monsoon season, indicating groundwater suitable for irrigation. The major facies observed in groundwater are mixed Ca–Mg–Cl, CaHCO3, and Ca–Mg–Cl type. Gibbs's diagram depicts that the maximum groundwater samples belonged to the evaporation–crystallization zone, which raises salinity by raising sodium and chloride concerning the increase of total dissolved solids. The results showed that the majority of the samples are suitable for irrigation, and the suitability improves during the post-monsoon season. HIGHLIGHTS Graphical illustration techniques such as United States Salinity Laboratory (USSL) diagram, Piper, Gibbs, Wilcox, and Chadha diagram are used.; Water indices sodium adsorption ratio, %Na, electrical conductivity, residual sodium carbonate, SSP, Kelly's ratio, and permeability index are within acceptable limits for agriculture use.; The water belongs to the C1S1 group, the Calcite type of water.; The Piper diagram explores the dominance of hydrochemical facies in the study area.;